Mechanical Power of DC Motors with Polygarmonic Power Supply - Kovalov V; Kovalova Yu.; Shcherbak I. (Problems of the Regional Energetics)
The aim of the work is to develop a method for determining the mechanical power of DC mo-tors when they are powered by semiconductor converters, since the harmonic components of the armature current do not create a torque on the shaft. This means that at the nominal electric power of the motor, it is necessary to reduce the mechanical power to ensure the nominal tem-perature regime of the armature winding. The aim is achieved by solving the problem of deter-mining the dependence of the mechanical power of the motor on the armature current pulsations factor, the value of which depends on the control parameter of the thyristor or transistor con-verter, on the inductance of the armature circuit and the load current. As a result, it was pro-posed to express the dependence of the mechanical power in terms of the allowable mechanical load factor, which, in turn, depends on the armature current pulsations factor. The method is as follows: 1) on a computer model determine the armature current pulsations factor; 2) determine the allowable mechanical load factor and the allowable mechanical power. The novelty of the work lies in the fact that the expression for determining the allowable mechanical load of DC motors with polyharmonic power has been further developed, which, unlike the known ones, contains the square of the armature current pulsations factor. An example of the practical use of the proposed method for calculating the allowable mechanical power of DC motor when pow-ered by single-phase thyristor rectifier.